Cancer da mama: análise de fatores de risco sob a perspectiva da teoria de Kurt Lewin - Almeida, Ana Maria de (1991)
The objective of this study was to study the risk factors of women with breast cancer in the region of Ribeirão Preto, SP. A retrospective study was made to analyze the main risk factors for the local population described in the literature. The theory of Kurt Lewin was used for a more comprehensive analysis of the variables. Using this approach, it was possible to identify several mutual relationship vectors for having breast cancer. The necessity of pointing out the interrelationshfp between forces which occur during a woman's life and which predispose her to breast cancer became evident.